Estudos conformacionais em compostos contendo íons lantanídeos - Oliveira, Maria Weruska Pereira de (2008)
Lanthanide macrocyclic complexes, especially containing Gd(III) ions, are largely used as contrast agents in the medical diagnostic technique named Magnetic Resonance Imaging (MRI). Theoretical investigation of these compounds by molecular modeling methods is an emerging research area today. In this work we have performed a conformational study of the following supramolecular compounds: the macrocyclic ligands 1,4,7,10- tetraazacyclododecane (DOTA) and 1,4,7,10-tetraazacyclododecane- 1,4,7,10-tetraacetic acid (H4DOTA) and the macrocyclic complexes [Gd(DOTA).H2O]- and Gd(PhenHDO3A).H2O, where PhenHDO3A is (rel-10- [(5R,6R)-5,6-dihydro-6-hydroxy-1,10-Phenanthroline-5-yl)-1,4,7,10- tetraazacyclododecane-1,4,7-triacetic acid). For this, we have developed and carried out a procedure that involves: (1) the sampling of the conformation space of these compounds through some short molecular dynamics at different temperatures and (2) full geometry optimization in the geometries obtained in the previous stage using semi-empirical AM1 method for the macrocyclic ligands and Sparkle/AM1 model for the macrocyclic lanthanide complexes. Our results revealed that the high flexibility of non-coordinated macrocyclic ligands DOTA and H4DOTA, helped us to test the ability of our methodology to sample different regions of conformation space of these compounds. For the [Gd(DOTA).H2O]- complex, we were capable to find the same conformational isomers which were reported in published works as well as to comprehend relevant details about the mobility of the coordinated water molecule. Furthermore, we also were capable to identify some intermediate local minima related to the dynamics of rotation of the coordinated acetate groups in the studied complexes as well as to the dynamics of ring inversion of the coordinated tetraazadodecane moiety in the Gd(PhenHDO3A).H2O. In conclusion, we possess now an interesting strategy to conduct the search for conformational isomers of these compounds. This knowledge is very important to be applied in the rational design of new molecules to act as contrast agent in MRI.